Changes in the carbon source and storage in a cultivation area of macro-algae in Southeast China. (March 2023) - Wang, Yingying; Yang, Weifeng; Zhao, Xiufeng; Zhang, Qinghua; Chen, Hansen; Fang, Ziming; Zheng, Minfang
Abstract: Macro-algae culture has recently attracted attention in China because of its capability to sequester carbon. Here, radionuclides, total organic carbon (TOC), and nitrogen (TN) were examined in a cultivation area of macro-algae in Southeast China. At the reference site, the ratio of TOC to TN (C/N, 8.1 ± 0.2, mean ± SD) did not exhibit discernible variation over the past 70 years. In contrast, in the cultivation area, C/N descended from 9.0 ± 0.2 around 1960 to 8.3 ± 0.2 between 1960 and 1990 and 7.6 ± 0.2 after 1990, coincident with the recorded kelp production in this area, indicating an influence of macro-algae culture-associated activities on carbon origin. Using a model, algal culture-associated activities contributed 23 ± 7 % between 1963 and 1990 and 53 ± 8 % between 1990 and 2022 to TOC. The burial of culture-associated TOC varied from 0.15 to 1.23 mg-C cm −2 yr −1, implying the unneglectable influence on carbon storage. Highlights: Changes in carbon source were observed in a macro-algae culture area in China. Temporal pattern of carbon source matched kelp production in the culture field. Burial flux of algae culture-associated carbon increased with kelp production.